Romeo & Juliet - Zeffirelli, Franco; Paramount Pictures (Firm). ([s.l.] Paramount Pictures, 1968)
Italian director Franco Zeffirelli stunned the screen world when he cast two young unknowns to portray the star-crossed lovers in Romeo & Juliet, but it was a gable that resulted in one of the most popular motion pictures of all time, winning international acclaim and four Academy Award nominations. Shakespeare's classic romance comes to stunning visual life in a refreshingly modern interpretation, bringing new vitality and insight to the most enduring love story ever written.
VCD
Franco Brusati and Masolino D'Amico, screenplay ; Anthony Havelock-allan and John Brabourne, producer ; Franco Zeffirelli, director.
Olivia Hussey, Leonard Writing, John McEnery.
Keywords: Feature Films; Love stories